Craft Today USA. - Smith, Paul J. (New York : American Craft Museum, 1989)
Aguado, Deborah ; Akers, Adela ; Anderson, Douglas ; Autio, Rudy ; Babcock, John ; Bacerra, Ralph ; Baldwin, Phillip ; Barnes, Dorothy Gill ; Barzel, Dina ; Basa, Lynn ; Bennett, Garry Knox ; Bennett, James A. ; Bero, Mary ; Berry, Carol ; Bird, Mike ; Bonner, Jonathan ; Bowen, Gaza ; Brooks, Jon ; Burak, Edward Fredrick ; Cacicedo, Jean williams ; Carlson, William ; Castle, Wendell ; Chase, Debra ; Chihuly, Dale ; Choo, Chunghi ; Cohen, Mardi-Jo ; Cohn, Michael ; Cook, Lia ; Crow, Nancy ; dailey, Dan ; Daley, William P. ; Day, Emmett ; dean, Peter S. ; Delisle, Roseline ; Deller, Harris ; Devore, Richard E. ; Dimare, Dominic L. ; Dondoghue, John M. ; Dreisbach, Fritz ; Duckworth, Ruth ; Earl, Jack ; Ebendorf, Robert ; Eberle, Edward S. ; Edwards, Stephen Dale ; Elliott, Lillian ; Ellsworth, David ; Elston, Theodora ; Fisch, Arline M. ; Flynn, Pat ; Frey, Viola ; Friedlich, Donald ; Garrett, John G. ; Gralnick, Lisa ; Grifffin, Gary S. ; Halem, Henry ; Hamlet, Susan H. ; Harding, Tim ; Hedstrom, Ana Lisa ; Hill, Julia ; Holder, Tina Fung ; Hu, Mary Lee ; Itter, Diane ; Jacobs, Ferne ; James, Michael ; Jr., Russell C. Jaqua ; Joyce, Tom ; Kallenberger, Kreg ; Kaneko, Jun ; Kaufman, Glen ; Kehlmann, Robert ; Kent, Ronald E. ; Kirkpatrick, Joey ; Klein, Alice H. ; Kling, Candace ; Kottler, Howard ; Kozel, Ina ; Krasnican, Susie ; Kraynek-Prince, Fran ; Lackey, Jane ; Levine, Marilyn ; Lipkin, Janet ; Litsios, Gregory ; Littleton, Harvey K. ; Loeber, Ken ; Loeser, Thomas ; Loloma, Charles ; Long, Randy J. ; Look, Dona ; Lucero, Michael ; lundberg, Tom ; Macdonald, Linda ; Mace, Flora C. ; MacNeil, Linda ; Makins, James D. ; Maloof, Sam ; Mann, Thomas ; Manuel, K. Lee ; Marioni, Dante ; Marks, Graham ; Marquis, Richard ; Marshall, John C. ; Maruyama, Wendy ; etc.
Craft Today USA. Organized by the American Craft Museum, New York, New York. A Cultural Presentation of the United States of America. Sponsored by Philip Morris International Inc. It is the first extensive collection of American work in craft to tour internationally to twelve countries.
Engels
boek
Keywords: U.S.A.